Leucine mediates cognitive dysfunction in early life stress-induced mental disorders by activating autophagy - Wang, Xiaotian; Wang, Xue; Xie, Fang; Sun, Zhaowei; Guo, Bomin; Li, Feng; Wang, Shida; Wang, Ying; Tian, Yingrui; Zhao, Yun; Qian, Lingjia (Frontiers in Cellular Neuroscience, 2023)
Objectives To explore the relationship between leucine in cerebrospinal fluid (CSF) and cognitive dysfunction in rats with early life stress (ELS) induced mental illness, and pathophysiological mechanism involved. Methods The maternal separation (MS), an animal paradigm used widely as a preclinical model of ELS which is one of the important risk factors for mental disorders. Behavioral experiments including open-field test, sucrose preference, object recognition and Morris water maze tests, Nissl staining, transmission electron microscopy and WES were employed in the present study. Results The behavioral results showed that MS rats were more prone to cognitive impairment and depression-and-anxiety-like behaviors than controls, including spatial self-exploration ability, memory ability, and spatial learning and memory function. Nissl staining analysis indicated that the number of neurons in the CA1 and CA3 regions of the hippocampus significantly decreased and the arrangement of nerve cells was abnormal. The leucine levels were decreased in the CSF of MS rats and highly correlated with the number of hippocampal neurons, and yet leucine supplementation improved the degree of MS-induced cognitive impairment. Furthermore, there were autophagosomes in the hippocampus of the low-leucine diet rats of the control and MS group but not in the high-leucine diet MS group by transmission electron microscopy. The protein expression of Beclin-1 in the hippocampus was significantly increased in the MS normal diet group and MS low-leucine diet group, yet decreased in the MS high-leucine diet group compared with the MS low-leucine diet group. Meanwhile, the Bcl-2/Bax ratio was significantly decreased in the control low-leucine diet group, MS normal diet group and MS low-leucine diet group. Ultimately, in vitro experiments suggested that leucine deficiency could activate neuronal autophagy including enhanced LC3II/LC3I and mRFP-GFP-LC3, which was consistent with the in vivo results, and the cell apoptosis rate and lactate dehydrogenase (LDH) cytotoxicity were also increased with leucine deficiency, while the above effects could be partly reversed by autophagy inhibitor treatment. Conclusions MS model caused adult male rats to be susceptible to cognitive dysfunction, which may regulate autophagy in hippocampal neurons through leucine metabolism in CSF.